2008
DOI: 10.2165/0002512-200825110-00005
|View full text |Cite
|
Sign up to set email alerts
|

Appropriateness of Prescribing among Elderly Patients in a Dutch Residential Home

Abstract: This study provides evidence supporting the formal integration of a clinical pharmacist into the healthcare team with the aim of improving prescribing appropriateness for institutionalized elderly Dutch patients. Overall MAI scores for all long-term medications used by a group of elderly patients improved significantly after a pharmacist-led medication review. This is an important finding because quality of prescribing is assuming increasing importance as a means of preventing avoidable medication-related harm. Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
25
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(34 citation statements)
references
References 23 publications
4
25
1
Order By: Relevance
“…Our results are similar to those obtained by other authors in reference to the degree of acceptation of the pharmacist's proposed changes (around 70%) and the kind of drugs usually used in DRPs, the alimentary tract and metabolism, Cardiovascular and nervous system being the main classes involved in the interventions 2 11…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…Our results are similar to those obtained by other authors in reference to the degree of acceptation of the pharmacist's proposed changes (around 70%) and the kind of drugs usually used in DRPs, the alimentary tract and metabolism, Cardiovascular and nervous system being the main classes involved in the interventions 2 11…”
Section: Discussionsupporting
confidence: 91%
“…The MAI score has showed that interventions have produced an improvement in the pharmacological profile of our patients; however, we avoid comparing the score with other scores as it is known that variations in scores depend on the context 2 3…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These patients were recruited for a medication review investigation throughout a period of 12 months over the period April 2003 until April 2004 and described elsewhere [11]. Briefly, those persons took an average of five regularly scheduled drugs making a total of at least 80 medications.…”
Section: Setting and Study Populationmentioning
confidence: 99%
“…With studies confirming the benefits of pharmacy-based patient care services to promote appropriate, safe and effective use of medications among elderly patients, expanding the institutional APPE sites to include Long-Term Care (LTC) facilities seemed a sensible solution to address capacity issues [8-14]. However, including LTC facilities as APPE sites remained problematic since the majority were serviced by off-site community pharmacists offering medication dispensing services remotely, with on-site time limited to once a week for patient care services.…”
Section: Introductionmentioning
confidence: 99%